Connections between Cognitive Impairment and Atrial Fibrillation in Patients with Diabetes Mellitus Type 2 - Marius Militaru; Daniel Florin Lighezan; Cristina Tudoran; Anda Gabriela Militaru (Biomedicines, 2024)
(1) Background: Cognitive decline (CD), considered a precursory state of dementia, is frequently encountered in patients with diabetes mellitus type 2 (DM-2) and might even have a higher prevalence in those with associated atrial fibrillation (AF). In this study, we aimed to research if the association of DM-2 and AF favors a precocious onset of CD. (2) Methods: This study was conducted on 160 patients, featuring 50 with DM-2, 54 with DM-2 and AF, and 56 subjects without DM-2 and AF, all evaluated clinically and with five neuropsychiatric scales. (3) Results: The Mini-Mental-State-Examination (MMSE), Montreal Cognitive Assessment (MoCA), Activities of Daily Living Score (ADL), Instrumental Activities of Daily Living Score (IADL), and Geriatric Depression Scale (GDS-15) were significantly altered in patients with DM-2 and AF in comparison to patients without these diseases. The logistic regression model indicated that, in patients with DM-2 and AF, an increase of one year in age is associated with a 7.3% augmentation of the risk of a precocious onset of CD (MMSE < 27). (4) Conclusions: CD is more frequent in patients with DM-2, especially when associated with AF, versus those without DM-2 and AF. Our findings suggest that an older age and associated dyslipidemia represent risk factors for CD in patients with DM-2.